Estudo histológico qualitativo e quantitativo das alterações na matriz extracelular (MEC) e estudo imuno-histoquímico do infiltrado inflamatório em doenças granulomatosas infecciosas e não infecciosas - Lucas Diego Gomes Bernardo (2023)
Qualitative and quantitative histological study of alterations in the extracellular matrix (ECM) and immunohistochemistry of the inflammatory infiltrate in infectious and non-infectious granulomatous diseases. Processes of organization and fibrosis (collagenogenesis) and/or elastic tissue synthesis or degradation occur in infectious and non-infectious cutaneous granulomatous diseases characterizing, profound Extracellular Matrix (ECM) alterations. Activity of macrophage subtypes contributes to these ECM changes and to fibrosis processes arising from the secretion of various cytokines, inflammatory activity, or ECM remodeling proteins such as the metalloproteases MMPs, collagen secretion and others. In view of the versatility and plasticity of this cell against agents, the mapping of macrophage expressed proteins such as CD68 and CD163 are investigated. Additionally, some mesenchymal markers such as alpha-actin and vimentin may indicate activation of cells with fibroblastic potential, i.e. activated collagen-producing fibroblasts ("myofibroblast"). Some quantitative techniques of specific components of the ECM such as reticular fibers (composed mainly of collagens I and III) and elastic fibers, provide clues as to how the ECM behaves in different models of granulomatous diseases of infectious causes such as tegumentary American leishmaniasis - ATL, Virchowian leprosy and paracoccidioidomycosis and also non-infectious diseases such as foreign body granuloma and sarcoidosis, establishing a comparison between these models. Thus, our study demonstrated a higher expression of alpha-actin, vimentin, and reticular fibers in the samples from the paracoccidioidomycosis and foreign body granuloma groups, along with higher rates of M2 macrophages (CD163 positive cells). Alterations in the elastic tissue occurred mainly in the samples from Virchowian leprosy and ATL. However, differences between infectious and non-infectious granulomatous diseases regarding the amount of M2 macrophages, reticular fibers, alpha-actin, and vimentin were not observed.